2022
DOI: 10.1002/nop2.1261
|View full text |Cite
|
Sign up to set email alerts
|

To support self‐management for people with long‐term conditions – The effect on shared decision‐making, empowerment and coping after participating in group‐learning sessions

Abstract: Introduction Interventions that support patients to handle the emotional and medical aspects of a long‐term health condition is important. One way is to use peer‐support groups, to help patients solving problems, increasing their knowledge and making decisions. Aim was to investigate the impact on shared decision‐making, empowerment and coping after participation in group‐learning sessions for patients with long‐term conditions ( N = 42). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Additionally, prior studies in other settings found that higher DES-SF scores are associated with higher levels of social support and higher usage of a digital remote monitoring platform [ 34 , 41 ]. Other clinical and real-world studies showed changes in DES scores before and after an intervention, suggesting that this could be used as an evaluation tool for DSMES programs or other interventions [ 39 42 ]. For example, in one published study, 61% of the participants had improvement in mean DES-SF scores from 3.90 (pre-intervention) to 4.30 (post-intervention) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, prior studies in other settings found that higher DES-SF scores are associated with higher levels of social support and higher usage of a digital remote monitoring platform [ 34 , 41 ]. Other clinical and real-world studies showed changes in DES scores before and after an intervention, suggesting that this could be used as an evaluation tool for DSMES programs or other interventions [ 39 42 ]. For example, in one published study, 61% of the participants had improvement in mean DES-SF scores from 3.90 (pre-intervention) to 4.30 (post-intervention) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two validated questionnaires, Diabetes Empowerment Scale Short Form (DES-SF), which is a measure of diabetes-related psychosocial self-efficacy, and Motivations and Attitudes Toward Changing Health (MATCH), can provide insight into an individual's self-reported empowerment and motivation [28,29]. The DES-SF has been used in cross-sectional surveys and clinical studies to measure the impact of interventions on diabetes empowerment [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. While DES-SF is specific to diabetes, MATCH is designed to assess general attitudes towards changing health behaviors, regardless of clinical condition [28,29].…”
Section: Introductionmentioning
confidence: 99%